Natural aggregate replacement by recycled materials in concrete production - Junak, Jozef; Stevulova, Nadezda (Видавництво Львівської політехніки, 2013)
In this contribution is presented overview of aggregate from recycled concrete and steel making slag treatment in civil engineering industry. The goal of experiments is utilization of these wastes as the partial or complete replacement of natural aggregates fraction 4-8 and 8-16 mm in concrete. Partial replacement was carried out from 20 to 80%. Зроблено огляд наповнювача з переробленого бетону і сталеплавильного шлаку в будівельній галузі. Метою експериментів є використання цих відходів як часткової або повної заміни в бетоні природного заповнювача фракцій 4-8 і 8-16 мм. Часткова заміна проводилася у розмірі від 20 до 80%.
Keywords: recycled concrete aggregate; steelma king slag; concrete; compressive strength; заповнювач до бетону; сталеплавильний шлак; бетон; міцність на стиск